LIBRARY PROFESSIONALS AND SOCIAL NETWORK SITES: EVIDENCE OF USE, RELEVANCE AND CHALLENGES FROM UNIVERSITY LIBRARIES IN OGUN STATE, NIGERIA. - Idiegbeyan-ose, Jerome; Ifijeh, Goodluck; Segun-Adeniran, Chidi; Fagbohun, Michael; Esse, Ugwunwa (DESIDOC Journal of Library & Information Technology, 2016)
This study investigated the use of social network sites among library professionals in University Libraries in Ogun State, Southwest Nigeria. The study population consisted of seventy-eight librarians in four Universities in the state. Questionnaires (which was the instrument for data collection) was administered to the entire population, out of which 55 (representing 70.5% response rate) were filled, returned and analysed for the study. The study revealed that library professionals do make use of social network sites. The most frequently visited social network site was Linkedln (58.2%). The respondents also indicated that they visited social network sites for the purpose of connecting and collaborating with friends and colleagues, carrying out current awareness and reference services to library users etc. Majority of the respondents (94.5%) in the study further revealed that the greatest challenge to the use of social network sites was lack of social media skills. The first hypothesis tested in the study indicated that there was moderate positive significant relationship between device used for internet access and use of social network sites (r=.408**, N= 55, p<.002.). The second hypothesis revealed that there was no significant relationship between gender and use of social network sites (r = .157, N=55, p >.05). The study was concluded with recommendations that library professionals should undergo training in social media skills among others.